THE INFLUENCE OF PRODUCT QUALITY AND BRAND IMAGE ON PURCHASING DECISIONS FOR LEMANK BATOK IN TEBING TINGGI CITY - Rusmewahni, Rusmewahni (RADJA PUBLIKA, 2022)
This study aims to analyze and examine the effect of product quality and brand image on purchasing decisions for lemang shells in the city of cliffs. The population in this study were all consumers of Lemang Batok Cliff City, totaling 96 people. The source of data in this study comes from primary data, namely the results of a questionnaire/questionnaire that is filled in directly by the respondent. Hypothesis testing using multiple regression analysis. The results of this study indicate that: (1.) The first hypothesis proposed states that the first hypothesis is accepted, meaning that the Product Quality variable (X1) has an effect on the Purchase Decision variable (Y). (2.) The second hypothesis proposed states that both are rejected, meaning that the Brand Image variable (X2) has no effect on the Purchase Decision variable (Y). (3. ) The third hypothesis proposed states that the variable Product Quality (X1) and Brand Image (X2) have an effect on the Purchasing Decision variable (Y). Keywords: Product Quality, Brand Image and Purchase Decision